Aquaculture management - Meade, James W. (Chapman & hall, 1989)
This text shows how to increase the effectiveness of aquaculture operations across the board. Serving as both a field manual for professionals and a textbook for aquaculture students, it aims to cover all aspects of aquaculture - from production and management to marketing and ethical considerations.